1998
DOI: 10.1200/jco.1998.16.12.3774
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immunophenotypic detection of minimal residual disease in acute lymphoblastic leukemia.

Abstract: Multiparametric flow cytometry of MRD in ALL patients is a valuable tool for relapse prediction and for the identification of a cohort of patients with very poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
100
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 22 publications
1
100
0
2
Order By: Relevance
“…This may explain the relatively low incidence found in the present study using sensitive CD33-PE and CD13-PE conjugates, as compared to some other reports in the literature. 11,[30][31][32][33] It is obvious from our study that the immunophenotypes of T-ALL differ significantly from normal BM T cells and NK cells. For a major part this is caused by their thymocyte origin (see ectopic antigen expression, Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the relatively low incidence found in the present study using sensitive CD33-PE and CD13-PE conjugates, as compared to some other reports in the literature. 11,[30][31][32][33] It is obvious from our study that the immunophenotypes of T-ALL differ significantly from normal BM T cells and NK cells. For a major part this is caused by their thymocyte origin (see ectopic antigen expression, Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] A cooperative study conducted by six European centers involved in the BIOMED-1 Concerted Action 'Investigation of Minimal Residual Disease in Acute Leukemia: International Standardization and Clinical Evaluation' applied multiparameter flow cytometry in which triple antibody combinations were used together with sensitive data acquisition methods (such as 'live gate' acquisition). Using this approach we obtained detailed information on cell subsets that are present in normal BM at very low frequencies and that may remain undetected using conventional methods of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] However, more recent studies have shown that by far the majority, if not all, precursor B-ALL cells display immunophenotypic features which are usually not detected in the normal bone marrow B cell precursors -the so-called phenotypic aberrations. [19][20][21][22][23] Accordingly, cross-lineage antigen expression and aberrant patterns of B cell maturation are usually detected in these patients. Based on these findings, it has been suggested that these leukemia-associated phenotypes could reflect, at least to a certain extent, the genetic aberrations present in the leukemic cells; accordingly for those patients displaying an identical genetic lesion, a similar phenotypic behavior could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, in recent years several reports have shown that in most precursor B-ALL cases neoplastic cells display aberrant phenotypes. [19][20][21][22][23] Some of these leukemia-associated phenotypes have been associated with specific genetic abnormalities. [24][25][26][27][28][29] In this regard, large multicentric studies have been conducted in order to explore the potential existence of an association between specific cytogenetic abnormalities such as the t(1;19)(q23;p13) [30][31][32] and t(4;11)(q21;p23) 33,34 translocations and peculiar phenotypes of leukemic B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative estimation of residual disease may improve prognostic evaluation. [17][18][19][20] Further studies are needed to evaluate the prognostic strength of minimal residual disease and to determine if intensification of treatment will alter the prognosis for this group of patients.…”
Section: Discussionmentioning
confidence: 99%